The Effect of Uric Acid to High Density Lipoprotein Cholesterol Ratio on Prognosis in Diffuse Large B Cell Lymphoma - Ilkkilic, Kadir; Sen, Bayram (The European Research Journal, 2026)
Objectives: International prognostic index (IPI) score, genetic mutation heterogeneity and inflammatory markers play an important role in predicting prognosis in diffuse large B-cell lymphoma (DLBCL). The uric acid to high-density lipoprotein cholesterol ratio (UHR) has been shown to be a new marker that allows better prediction of metabolic deterioration and inflammatory processes. The aim of the study is to evaluate the effect of UHR on prognosis in DLBCL patients. Methods: In this retrospective cohort study, 120 patients were included. The effects of UHR on prognosis were evaluated. Results: Of the total cohort, 79 patients survived, whereas 41 patients died. Mortality was higher in patients with higher UHR and IPI score ≥ 3 (P=0.047 and P=0.001, respectively). Univariate analysis revealed that age, Eastern Cooperative Oncology Group performance status (ECOG PS), disease stage, extranodal involvement, uric acid levels, IPI score, and UHR were significant predictors of mortality. Multivariate analysis revealed that ECOG PS, IPI score, and UHR were found to be independent predictors. Kaplan-Meier analysis showed that higher UHR (>0.1075) and IPI scores (≥3) were associated with decreased overall survival. (P=0.003 and P=0.005, respectively). Conclusions: Elevated pre-treatment UHR independently predicts prognosis and is associated with reduced overall survival in patients with DLBCL. It may serve as a surrogate marker of systemic metabolic dysfunction and help identify high-risk patients alongside the IPI score.